2021
DOI: 10.3892/etm.2021.11091
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin inhibits high glucose‑induced inflammation, oxidative stress and apoptosis in podocytes by activating the AMPK/Nrf2 signaling pathway

Abstract: Diabetic nephropathy (DN) is a serious and common complication of type 1 and 2 diabetes. Gastrodin has been reported to suppress high glucose (HG)-induced inflammation and oxidative stress in vivo and in vitro. However, the effect of gastrodin on DN has not been fully elucidated. The present study aimed to investigate the underlying mechanism involved in the effect of gastrodin on podocyte injury caused by DN. Cell viability was evaluated using Cell Counting Kit-8 assay and secretion levels of TNF-α, IL-1β and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…AMPK phosphorylation was also followed by upregulation of ULK1, enhancement of autophagy, and decrease in oxidative stress, podocyte loss, fibrosis, and albuminuria in a mouse model of diabetic nephropathy [125]. Conversely, inhibition of AMPK by compound C abolished the beneficial effects of AMPK in podocyte viability and aggravated high glucosemediated oxidative stress, inflammation, apoptosis, collagen accumulation, and GMB thickening (Figure 2) [126,127]. Decreased function of PGC-1α was shown to impair mitochondrial function and facilitate fibrogenesis in diabetic nephropathy [128].…”
Section: What Is the Effect Of Downstreammentioning
confidence: 95%
“…AMPK phosphorylation was also followed by upregulation of ULK1, enhancement of autophagy, and decrease in oxidative stress, podocyte loss, fibrosis, and albuminuria in a mouse model of diabetic nephropathy [125]. Conversely, inhibition of AMPK by compound C abolished the beneficial effects of AMPK in podocyte viability and aggravated high glucosemediated oxidative stress, inflammation, apoptosis, collagen accumulation, and GMB thickening (Figure 2) [126,127]. Decreased function of PGC-1α was shown to impair mitochondrial function and facilitate fibrogenesis in diabetic nephropathy [128].…”
Section: What Is the Effect Of Downstreammentioning
confidence: 95%
“…Huang et al found that gastrodin increased the activity of antioxidant enzymes and reduced the level of inflammatory factors, thus reducing the inflammation, oxidative stress, and apoptosis of MPC-5 cells induced by HG. The mechanism is related to activating the AMPK/Nrf2 signaling pathway and reducing the formation of NLRP3 inflammasome [ 71 ]. Gastrodin is relatively safe to use.…”
Section: Natural Compoundsmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 , 12 AMP-activated protein kinase (AMPK) acts as an energy sensor in the majority of mammalian cells and is stimulated by low ATP levels or a high ratio of AMP/ADP to ATP. 13 , 14 Interestingly, suppression of AMPK was implicated in DOX-induced cardiac, hepatic, and renal damage whereas genetic or pharmacological activation of these molecules improved organs’ structure and function by attenuating oxidative stress, fibrosis, inflammation, and apoptosis. 13 , 15 , 16 In this context, it was shown that AMPK stimulates antioxidant expressions by upregulating and activating Nrf2.…”
Section: Introductionmentioning
confidence: 99%